The Influence of Celebrity Endorsers, Brand Image, and Brand Awareness on Purchase Decisions with Purchase Interest as a Product Mediator of MS Glow for Men - Sedana, I Made Rai Arya; Mahyuni, Luh Putu (PT Mattawang Mediatama Solution, 2024)
The aims of this research is to determine the influence of celebrity endorsers and brand image on brand awareness on purchase decisions for MS Glow for Men products. This type of research is quantitative using secondary data via Instagram online. The population in this study involved all users of Ms Glow for Men products in Denpasar City (Ms. Glow for Man, Denpasar). The sample in this study by 144 respondents. The data collection technique questionnaires using the Google form. Data processing for descriptive analysis used SPSS statistical application software and analyzed using SElM with the help of Partial Least Squares (PLS) software. Celebrity endorsers and brand image have a positive and significant influence on consumer purchase decisions and consumer purchase interest. Brand awareness has a positive and significant influence on consumer purchase decisions and consumer purchase interest. Purchase interest has a positive and significant influence on consumer purchase decisions. The relationship between the brand image construct and purchase decisions can be mediated by the purchase interest construct. Then, the relationship between the celebrity endorser construct and purchase decisions can be mediated by the purchase interest construct. The results of this analysis indicate that the better the endorser's ability to introduce and promote products as consumers' purchase interest increases, this will also increase their purchase decisions.